Infrared Red Intubation System (IRRIS) guided flexile videoscope assisted difficult airway management. Issue 1 (24th October 2017) - Kristensen, M. S.; Fried, E.; Biro, P.
Abstract : Background: Tracheal intubation with a flexible scope is a cornerstone technique in patients with severely difficult airways, but may fail. We report on a technique, Infrared Red Intubation System (IRRIS), that seems to facilitate the identification of the glottis. Methods: The IRRIS is placed over the patient's cricothyroid membrane and emits blinking infrared light through the patient's skin into the subglottic space. When a flexible videoscope (one that does not filter infrared light) is introduced into the airway, it will display this as a blinking white light emerging from the glottis, retrograde transillumination, showing the pathway to the trachea. We have introduced this as an adjunct when managing our patients with difficult airways. We describe the technique and retrospectively report on the first ten patients where it was used. Results: All ten patients had significant pathology in the airway, radiation therapy, predictors for difficult intubation and/or morbid obesity. In all cases the blinking light was visible during the flexible endoscopy and provided unambiguous identification of the glottis, from a distance. The blinking nature of the light from the IRRIS helped to distinguish it from the reflections in the mucosa that inevitably arise when the mucosa is hit by the light from the flexible scope itself. Conclusion: The addition of the IRRIS technique to intubation with flexible videoscopes may be a tool that will make intubation of the most difficult airways easier and may be of special help to the clinician who only rarely uses flexible videoscopes for tracheal intubation.